(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This study aims to demonstrate the impact of monetary policy on economic growth by applying to the state of Iraq during the period 2003-2020. The analytical descriptive approach was relied on, using a standard model that was applied using time series and joint integration to show the impact of monetary policy.expressed in terms of the money supply (M1,M2,M3)on economic growthexpressed as an average per capita GDP)The study reached a number of results, the most important of which are; That time series is variableshe sawThe model is unstablee in the levelWhile he found thattime seriesstraightsee when takingfirst differences,Whichthat changes inIngredientsTheMnakedAnd thez cash(M1,M2,M3)emotionally affectThe average per capita share ofGDP,And theThere is a positive relationship and a clear effect in the short term and at a high levelybetween variableatThe independent and the dependent variable and then this effect begins to fade relatively with the passage of time in the long run. recommendTresearchereThe necessity of coordinating economic policies to increase economic growth rates to achieve comprehensive and sustainable development. At the end of this study, the researcher presented the results, recommendations and references on which the study relied